Sentiment and the Effectiveness of Technical Analysis: Evidence from the Hedge Fund Industry - Smith, David M.; Wang, Na; Wang, Ying; Zychowicz, Edward J. (Journal of Financial and Quantitative Analysis, 2016)
This article presents a unique test of the effectiveness of technical analysis in different sentiment environments by focusing on its usage by perhaps the most sophisticated and astute investors, namely, hedge fund managers. We document that during high-sentiment periods, hedge funds using technical analysis exhibit higher performance, lower risk, and superior market-timing ability than nonusers. The advantages of using technical analysis disappear or even reverse in low-sentiment periods. Our findings are consistent with the view that technical analysis is relatively more useful in high-sentiment periods with larger mispricing, which cannot be fully exploited by arbitrage activities because of short-sale impediments.